2016
DOI: 10.1002/slct.201601534
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Green Synthesis of 3,3′‐Spirooxindoles via Isatin–based One–pot Multicomponent Cascade Reactions in Aqueous Medium

Abstract: 3,3′‐spirooxindoles are important synthetic target compounds and play special role in organic chemistry because of their extensive biological activities and applications of pharmaceutical lead discovery. In recent years, there has been a significant increase in design of new, atom economical and eco‐friendly isatin‐based one‐pot multicomponent cascade reactions in aqueous medium for the green synthesis of 3,3′‐spirooxindoles. In this review, the recent advances in this area were summarized and classified accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(18 citation statements)
references
References 129 publications
0
18
0
Order By: Relevance
“…The use of green solvents or solvent‐free conditions instead of hazardous solvents in organic reactions, to avoid pollution from the environment, is enormously important in organic synthesis and water is an ideal choice. [ 35,36 ] Previous studies merely confirmed that the hydrogen bonds between water and substrates may accelerate many organic reactions. [ 37,38 ] Hence, herein we describe the green synthesis of spirooxindolopyrans, spirooxindoloxanthenes, and spirooxindolopyrimidines in the presence of a newly prepared organic–inorganic hybrid nanostructure (MNPs@SiO 2 @PUF@Zn) in aqueous conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The use of green solvents or solvent‐free conditions instead of hazardous solvents in organic reactions, to avoid pollution from the environment, is enormously important in organic synthesis and water is an ideal choice. [ 35,36 ] Previous studies merely confirmed that the hydrogen bonds between water and substrates may accelerate many organic reactions. [ 37,38 ] Hence, herein we describe the green synthesis of spirooxindolopyrans, spirooxindoloxanthenes, and spirooxindolopyrimidines in the presence of a newly prepared organic–inorganic hybrid nanostructure (MNPs@SiO 2 @PUF@Zn) in aqueous conditions.…”
Section: Introductionmentioning
confidence: 99%
“…According to the principals of green chemistry, designing the green reaction conditions has become an important subject for the elimination of pollution from the environment in recent years. In this regard, the use of solvent‐free conditions or green solvents in organic reactions instead of hazardous solvents has been developed enormously in organic synthesis . Multi‐component reactions (MCRs) are powerful tools in organic synthesis because of short time, clean and high yield, and atom economy .…”
Section: Introductionmentioning
confidence: 99%
“…Multi‐component reactions (MCRs) are powerful tools in organic synthesis because of short time, clean and high yield, and atom economy . These advantages have encouraged scientists to use MCRs for synthesis of natural products including spiropyrans, which show a variety of biological activities, such as anti‐cancer, anti‐HIV, anti‐microbial, anti‐tubercular, anti‐viral and anti‐fungus . Some examples of 3,3‐spirooxindole cores with inhibited activity have been presented in Scheme .…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, several protocols for the synthesis of isoxazoles and spirooxindoles have been reported [19][20][21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%